DAMPAK PENGGUNAAN TIKTOK TERHADAP PERILAKU BELAJAR PESERTA DIDIK - Rahmi,; Muhammad Djamil M. Nur,; M. Jen Ismail,; Siti Rabiatul Adawiyah, (Istiqra: jurnal hasil penelitian, 2025)
This study aims to examine the impact of TikTok usage on students’ learning behavior at MAN 1 Kota Palu. A qualitative approach was employed through interviews, observations, and documentation involving purposively selected teachers and students. The findings show that TikTok has both positive and negative influences. On the positive side, it provides entertainment, motivation, and encourages creativity. On the negative side, excessive use reduces concentration, disturbs study time, and weakens discipline. It is recommended that teachers and parents supervise and guide TikTok usage towards more productive purposes.